THE IMPACT OF THE CORPORATE FARMING PROGRAM ON THE PRODUCTIVITY AND INCOME OF THE BAROKAH FARMERS GROUP'S RICE FARMING BUSINESS - Perdana, Putri; Arianti, Yoesti (Universitas Veteran Bangun Nusantara, 2025)
Rice is a major food commodity that consistently draws attention, particularly in efforts to increase productivity and farm income. Various initiatives have been undertaken by both the government and the private sector to boost rice productivity in order to meet food demands. One such initiative is the Corporate Farming (CF) program, an agricultural institutional model based on the principle of consolidating land owned by members of farmer groups by removing the boundaries (galengan) between rice fields. The aim of the program is to enhance productivity through the use of better technology and to achieve more effective and efficient farming practices. This study aims to examine the impact of the CF program on the productivity and income of rice farming within the Barokah Farmer Group. The research employs a descriptive-analytical method, with the t-test used as the analytical tool. Data collection was conducted through surveys, with productivity and income serving as the main variables. The results show that the average productivity and income per hectare per season before and after the implementation of the CF program were significantly different. However, the changes had a negative value, indicating that the program did not have a positive impact. The average value of rice productivity per hectare per planting season after the implementation of CF was 2.455 tons per hectare, smaller than after the implementation of CF of 3.480 tons per hectare. Rice farming income per hectare per planting season after CF was IDR5,298,994.02, which was smaller than before CF, which was IDR12,433,806.81. This outcome is attributed to a shift in farming technology from conventional to organic methods which affected both productivity and farm income before and after the implementation of the CF program